The Role of Basic Attitude Techniques in Pencak Silat Learning to Improve PJOK Learning in Students: A Review of the Literature - Nubatonis, Jefrio Demitrimus; Neolaka, Erwin Sarnoto; Fufu, Ronald Dwi Ardian; Tajuddin, Al Ihzan; Alexander, Xander Faldo Ribut; Baer, Gillian (JSES : Journal of Sport and Exercise Science, 2026)
Purpose: This study aims to analyze the role of basic stance techniques in pencak silat learning to improve PJOK learning outcomes among students. Materials and Methods: This study employed a literature review approach by analyzing six selected scientific articles published within the last ten years. The data were collected from databases such as Google Scholar, PubMed, and ScienceDirect using keywords related to pencak silat, stance techniques, and PJOK learning. Result: The findings indicate that mastery of basic stance techniques significantly contributes to improving students’ motor skills, balance, coordination, and understanding of movement concepts. In addition, the use of instructional media such as video tutorials and interactive multimedia enhances student motivation and learning outcomes. Conclusion: Basic stance techniques play a fundamental role in improving the effectiveness of PJOK learning. Therefore, they should be emphasized as a core component in pencak silat instruction in schools.